Citizen Satisfaction with the Distribution of Disaster Logistic - Mashudi; Fauziah, Luluk; Windriya, Anafil (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
Departing from such condition as officer competency, compensation received, and service quality in distributing disaster logistic that has been relatively standardized, there is an indication that people affected by flood disaster have not been satisfied yet. This research aims to find out the citizen satisfaction level and the factors affecting their satisfaction. This research employed qualitative approach with survey research format. Data collection was carried out by distributing questionnaire to 68 respondents taken purposively and interviewing some respondents randomly. In addition, data collection was also conducted using documentation and observation techniques. Data was processed using percentage and multiple linear regression techniques with Statistical Program for the Social Science (SPSS) program. The result of research shows: 1) the satisfaction of citizens affected by flood is at moderate level; 2) officer competency, compensation, and service quality affect both partially and simultaneously the citizen satisfaction; 3) meanwhile, officer competency variable affects the citizen satisfaction most significantly; and 4) some other variables affect the citizen satisfaction slightly but excluded from this research.